HUBUNGAN PRAKTIK BUANG SAMPAH, PRAKTIK PENGGUNAAN INSEKTISIDA, CONTAINER INDEX, DAN LINGKUNGAN FISIK RUMAH DENGAN KEJADIAN DBD (STUDI DI EMPAT RUMAH SAKIT DI KOTA SEMARANG) - Nurul Fitria; Nur Endah Wahyuningsih; Retno Murwani (Jurnal Kesehatan Masyarakat (Undip), 2016)
Dengue Hemorrhagic Fever (DHF) is a major public health problem in Indonesia. This disease is caused by dengue virus and transmitted by the bite of Aedes aegypti mosquitoes. Dengue has spread widely throughout Indonesia, one of them is Semarang and the surrounding area. IR DHF Semarang from 2006 to 2015 is always higher than IR DHF Central Java and IR DHF National. This research was to analyze eliminating garbage practice, the insecticide use practice, container index, and home physical environment to incidence of DHF in four hospitals in Semarang City. This type of research was an observational analytic study using case control design. The population in this study were hospitalized dengue patients period March to May 2016 in four hospitals in Semarang City and health people (neighbor’s dengue patients) who lived in Semarang City and Demak Regency. Samples were 18 cases and 18 controls who had a vulnerable age (children aged 0-4 years and elderly aged >46 years) by using total sampling technique. The data was analyzed with chi-square test and odds ratio calculation with 95% confidence interval. The result showed that insignificant factors were eliminating garbage practice (p=0,289), insecticide use practice (p=0,737), container index (p=1,000), presence of breeding places (p=1,000), temperature in the house (p = 1,000), and humidity in the house (p=1,000). It can be concluded that there were not significant variables to the incidence of DHF in four hospitals in Semarang City.